ANALISIS PENGARUH KONVERGENSI IFRS TERHADAP MANAJEMEN LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Nastiti, Anggraini Dwi; Ratmono, Dwi (Diponegoro Journal of Accounting, 2015)
The research aimed to analyze the effect of the convergence of IFRS on earnings management by considering the characteristics of corporate governance as a moderating variable. Convergence of IFRS as an independent variable is proxied by using dummy variables. Earnings management is measured using the value of discretionary accruals. Mechanism of corporate governance as a moderating variable considering the characteristics of the commissioners, audit committee, auditor quality and the institutional ownership. This research uses a control variable size, profitability, leverage, and growth. The sample in this research is manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2013. The sampling method in this research is purposive sampling. The analysis technique in this study using multiple regression analysis. These results of this study indicate that convergence of IFRS have a significant influence on earnings management with a positive direction. The test results found that the application of IFRS can increase the level of earnings management firms. Thus after IFRS, companies tend to have this level of earnings management is higher. Corporate governance mechanism can moderate the effects of IFRS on earnings management. This is indicated by the effect of the accounting and financial expertise possessed by the audit committee in enhancing the positive effect of IFRS on earnings management.